2019
DOI: 10.1101/691006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decreased electrocortical temporal complexity distinguishes sleep from wakefulness

Abstract: In most mammals, the sleep-wake cycle is constituted by three behavioral states: wakefulness (W), non-NREM (NREM) sleep, and REM sleep. These states are associated with drastic changes in cognitive capacities, mostly determined by the function of the thalamo-cortical system. The intra-cranial electroencephalogram or electocorticogram (ECoG), is an important tool for measuring the changes in the thalamo-cortical activity during W and sleep. In the present study we analyzed broad-band ECoG recordings of the rat … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 37 publications
(51 reference statements)
2
20
0
Order By: Relevance
“…Furthermore, this effect might also contribute to a reduction in mixed states, hypomania, and autonomic hyperactivations that can occur in BD chronotherapy due to overapplication of light stimuli and medication. Additionally, methods for measuring the daily variation of frontal neural activity are now under development, with a focus on EEG approaches (Croce et al, 2018 ; González et al, 2019 ). These methods might contribute to the realization of a form of chronotherapy modulated by RRO feedback.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this effect might also contribute to a reduction in mixed states, hypomania, and autonomic hyperactivations that can occur in BD chronotherapy due to overapplication of light stimuli and medication. Additionally, methods for measuring the daily variation of frontal neural activity are now under development, with a focus on EEG approaches (Croce et al, 2018 ; González et al, 2019 ). These methods might contribute to the realization of a form of chronotherapy modulated by RRO feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we used competition between excitatory and inhibitory neurons in this study to describe long-term neural dynamics in the frontal cortex. However, the questions of what reflects the long-term dynamics of brain activity and what mechanism produces it are currently controversial (Croce et al, 2018 ; González et al, 2019 ). Therefore, it is important that our proposed method be verified with models based on other neural mechanisms for producing long-term neural dynamics in the frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work (2), we found that the ECoGs' temporal complexity decreased from wakefulness to sleep; i.e., the repertoire of dynamical motifs was reduced when the animals fell asleep ( Figure 1A, B and C). Interestingly, we observed this result in several cortical locations independent of its function (motor, olfactory, somatosensorial and visual), which suggested that the loss in temporal complexity was a global motif developed in the passage from W to sleep.…”
Section: Introductionmentioning
confidence: 68%
“…The animals were chronically implanted with electrodes to monitor the states of sleep and W. To record the ECoG, stainless steel screw electrodes were placed on the skull above motor (bilateral), somatosensory (bilateral), visual cortices (bilateral), the right olfactory bulb, and cerebellum, which was the reference electrode (see Fig. 1a and Table 2 in González et al 2019). A neck bipolar electrode was employed to record the EMG.…”
Section: Methodsmentioning
confidence: 99%
“…We employed surgical procedures similar to those used in our previous studies (Cavelli et al, 2018;Gonzalez et al, 2019;Mondino et al, 2019). The animals were chronically implanted with intracranial electrodes.…”
Section: Surgical Proceduresmentioning
confidence: 99%